Preparation of hard carbon with fast charging performance and application of hard carbon in sodium battery
By pretreating and pre-carbonizing the precursor of the hard carbon negative electrode material, the problem of poor rate performance of existing hard carbon materials is solved, and the preparation of hard carbon materials with a pore size of less than 1.7nm is realized, which improves the sodium ion battery Fast charging performance.
Patent Information
- Application Number
- CN202411647022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing hard carbon anode material has extremely slow sodium storage process below 0.05V, resulting in poor rate performance and is difficult to meet the needs of fast charging sodium ion batteries.
By pretreating the thermoplastic precursor and the thermoset precursor, different functional groups are added, so that the two react in the precarbonization process after mixing, affecting the degree of cross-linking of the precursor, so that the pore size is less than 1.7nm after carbonization , hard carbon material with a pore size factor exceeding 0.03.
It improves the rate performance of hard carbon materials and achieves excellent fast charging performance in sodium ion batteries, which is suitable for negative electrode materials for sodium ion secondary batteries.
Smart Images

Figure CN119461324A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a method for preparing a sodium ion battery negative electrode material with hard carbon having fast charging performance. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in portable electronic products and electric vehicles due to their long service life and high energy density. However, with the widespread use of lithium-ion batteries and the shortage and uneven distribution of lithium resources, the price of lithium has continued to rise, making it difficult to meet the growing demand of the electric vehicle market. In addition, the insufficient power density of lithium-ion batteries leads to long charging times, which triggers the problem of "charging anxiety". In particular, graphite anodes are prone to lithium precipitation during fast charging, which accelerates battery degradation and may cause safety hazards. In contrast, sodium resources are abundant, widely distributed and low in cost, making it a powerful supplement to lithium-ion batteries. Due to thermodynamic limitations, commercial graphite anode materials are difficult to effectively embed sodium ions, so graphite as anode materials for sodium-ion batteries shows almost no sodium storage activity. Therefore, the development of new high-capacity, low-cost anode materials is crucial for the commercialization of sodium-ion batteries.
[0003] Currently, common negative electrode materials for sodium-ion batteries include carbon-based materials, titanium-based materials, organic materials, and alloy materials. Among them, hard carbon materials are considered to be the most mature and most likely to be commercialized negative electrode materials for sodium-ion batteries due to their low operating voltage (<0.1V), low cost, and simple preparation. Nevertheless, due to the extremely slow sodium storage process of hard carbon below 0.05V, its rate performance is poor (the capacity drops by up to 60% at a current density of 1C), making it difficult to meet the market demand for fast-charging sodium-ion batteries. Therefore, designing and preparing hard carbon materials that still have a long platform capacity at high current density is of great significance for the realization of fast-charging sodium-ion batteries.
[0004] CN103094528A discloses a hard carbon negative electrode material for lithium-ion power and energy storage batteries, and its preparation method includes the following steps: using the pyrolysis product of a thermosetting resin or a mixture of a thermosetting resin and a thermoplastic resin as a hard carbon matrix, and using a carbon material as a coating to obtain a hard carbon negative electrode material. CN116425140A discloses a nitrogen-doped hard carbon material and its preparation method, including the following steps: 1) after mixing phenolic resin and melamine resin, under the action of a curing agent or a curing agent auxiliary, completing the preparation of a carbon source precursor; 2) heating the prepared carbon source precursor to 600-800°C at 5-10°C / min, and then heating it to 1200-1400°C at 0.5-5°C / min, completing carbonization, and obtaining a nitrogen-doped hard carbon material. CN116022769A discloses a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: (1) mixing a resin precursor and an alcohol solvent, adding zinc oxide, stirring, and curing to obtain a hard carbon precursor; (2) subjecting the hard carbon precursor obtained in step (1) to carbonization treatment under an inert atmosphere, and crushing, acid washing, and sieving to obtain the hard carbon negative electrode material for a sodium ion battery. The resin precursor comprises any one of a phenolic resin precursor, a furan resin precursor, or a furfural resin precursor, or a combination of at least two thereof, preferably a phenolic resin precursor; preferably, the phenolic resin comprises a thermoplastic phenolic resin and / or a thermosetting phenolic resin.
[0005] There are reports in the prior art of preparing hard carbon materials by compounding thermosetting resins and thermoplastic resins as precursors. However, the thermosetting and thermoplastic precursors are simply physically mixed and cannot be connected to each other at the molecular level. Ultimately, it can only increase the sodium storage capacity of the hard carbon, but cannot be modified at the molecular level to improve the rate performance of the hard carbon. Summary of the invention
[0006] In order to overcome the defect that the rate performance of hard carbon negative electrode materials in the prior art is not good enough, the present invention proposes a method for preparing hard carbon with a specific microstructure. The present invention pre-treats the thermoplastic precursor and the thermosetting precursor using different methods to add different functional groups to the two respectively. In the process of pre-carbonization after mixing, the macromolecular chains in the pre-treated thermoplastic and thermosetting precursors will undergo bonding reactions, affecting the degree of cross-linking of the precursors, thereby obtaining a hard carbon material with a pore size less than 1.7nm and an pore size factor exceeding 0.03 after carbonization. By mixing thermosetting and thermoplastic precursors in different proportions, the degree of cross-linking of the carbon layer during the calcination process is changed, and a hard carbon material with a pore size less than 1.7nm and an pore size factor exceeding 0.03 is obtained, thereby improving its rate performance, and then assembling a full battery to improve the fast charging performance of the sodium ion battery.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a fast-charging hard carbon negative electrode material comprises the following steps:
[0009] (S1) mixing a metal chloride with a thermoplastic precursor, heating and keeping the mixture in an oxygen-containing atmosphere to obtain a pretreated thermoplastic precursor; and curing the thermosetting precursor with an acidic curing agent to obtain a pretreated thermosetting precursor;
[0010] (S2) Mixing the pretreated thermoplastic precursor and the pretreated thermosetting precursor uniformly, pre-carbonizing them under an inert atmosphere; and then carbonizing them at a high temperature under an inert atmosphere or a hydrocarbon gas atmosphere to obtain a hard carbon material; the pretreated thermosetting precursor accounts for 50-90% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor.
[0011] Furthermore, in step (S1), the thermoplastic precursor is selected from at least one of polyvinyl chloride, polyaniline, asphalt, coal, and petroleum coke; the metal salt chlorination is selected from at least one of NaCl, KCl, ZnCl2, MgCl2, and CaCl2; and the mass ratio of the thermoplastic precursor to the metal salt chlorination is 1:0.5-1. The metal chloride salt catalyzes the polymerization of the precursor at high temperature and promotes the formation of carboxyl and carbonyl functional groups.
[0012] Furthermore, in step (S1), the thermosetting precursor is selected from at least one of phenolic resin, epoxy resin, sucrose, cellulose, and cotton; and the acidic curing agent is selected from at least one of oxalic acid, phosphoric acid, benzenesulfonic acid, tartaric acid, citric acid, and anhydrous benzoic acid. The mass ratio of the thermosetting precursor to the acidic curing agent is 1:0.1-0.3. The acidic curing agent increases the crosslinking degree of the precursor during the curing process and catalyzes the generation of hydroxyl functional groups.
[0013] Furthermore, in step (S1), the oxygen-containing atmosphere refers to an oxygen content greater than 20%, such as air, oxygen, or a mixture of air and oxygen; heating and heat preservation are carried out at a heating rate of 2-10°C / min to 200-300°C, and heat preservation is carried out for 5-10h.
[0014] Further, in step (S2), the pretreated thermosetting precursor accounts for 60-80% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor; preferably, the pretreated thermosetting precursor accounts for 70-80% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor.
[0015] More preferably, the thermosetting precursor is phenolic resin and epoxy resin, and the thermoplastic precursor is asphalt, which can obtain a hard carbon negative electrode material with optimal specific capacity and rate performance. The possible reason is that the thermoplastic precursor with a lower degree of cross-linking reacts with the thermosetting precursor with a higher degree of cross-linking when mixed, which not only reduces the overall degree of cross-linking, but also can produce a rich closed-pore structure in the subsequent carbonization process.
[0016] Furthermore, in step (S2), the mixing method is not particularly limited, including but not limited to ball milling, grinding, sand milling, etc. Preferably, the method is ball milling, with a ball-to-material ratio of 10-20:1, a rotation speed of 400-700 rpm, and a ball milling time of 3-10 hours.
[0017] Furthermore, in step (S2), the pre-carbonization is carried out under an inert atmosphere, the temperature is raised to 500-800°C and kept for 2-5 hours, the inert atmosphere is under an argon atmosphere, and the heating rate is 1-3°C / min; the inert atmosphere is at least one of nitrogen and argon.
[0018] Furthermore, in step (S2), the high temperature carbonization is carried out by heating the temperature to 1000-1700°C, preferably 1300-1500°C, at a heating rate of 5-10°C / min, and calcining for 5-10 hours.
[0019] The slow heating rate during pre-carbonization is conducive to the formation of a uniform and disordered cross-linked structure. On the contrary, if the heating rate is too fast, the cross-linking copolymerization is insufficient, which will cause the local polymer carbon to undergo direct polycondensation into mesophase carbon microspheres with sheet-like ordered polymers. Subsequent high-temperature calcination will generate long-range ordered and tightly stacked graphene layers, which is not conducive to the storage of sodium ions and is not conducive to improving the material capacity.
[0020] Furthermore, in step (S2), after the high temperature carbonization is completed, there is also an acid washing step, that is, the carbonized material is mixed and stirred in an inorganic acid for 10-24 hours, washed, and dried to obtain the hard carbon negative electrode material of the present invention. The purpose of acid washing is to remove impurities.
[0021] The present invention also provides a sodium ion battery negative electrode material, comprising a hard carbon material, a conductive additive, and a binder, wherein the hard carbon material is prepared by the above-mentioned preparation method.
[0022] The excellent effect of the present invention is to provide a method for preparing an organic polymer-based sodium ion battery negative electrode material and its application. The present invention uses low-priced and technologically mature industrial organic polymers as raw materials, increases the crosslinking degree of the precursor by pre-oxidation, and then mixes the pre-oxidized thermosetting precursor and thermoplastic precursor, which significantly improves the specific capacity and rate performance of the hard carbon material. The preparation method of the present invention is low-cost, simple in process, high in carbon yield, and suitable for large-scale production of hard carbon materials. It is also used as a negative electrode material in sodium ion secondary batteries. The thermoplastic precursor with a lower degree of crosslinking reacts with the thermosetting precursor with a higher degree of crosslinking when mixed, which not only reduces the overall degree of crosslinking, but also can produce a rich closed-cell structure in the subsequent carbonization process. Therefore, the obtained hard carbon material has excellent rate performance when used in sodium ion batteries, while also taking into account the platform capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the TEM image of the hard carbon material obtained in Example 1.
[0024] Figure 2 This is the TEM image of the hard carbon material obtained in Example 2.
[0025] Figure 3 This is the TEM image of the hard carbon material obtained in Example 3.
[0026] Figure 4 This is the TEM image of the hard carbon material obtained in Example 4.
[0027] Figure 5 This is the TEM image of the hard carbon material obtained in Example 5.
[0028] Figure 6 This is the small-angle X-ray scattering spectrum of the hard carbon material obtained in Example 3.
[0029] Figure 7 This is the small-angle X-ray scattering spectrum of the hard carbon material obtained in Example 6. DETAILED DESCRIPTION
[0030] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.
[0031] Example 1
[0032] (S1) Phenolic resin and oxalic acid in a mass ratio of 1:0.2 are dissolved in ethanol, heated and stirred on a heating table at 80° C. for 8 hours, and solidified particles are obtained after cooling as a pretreated thermosetting precursor.
[0033] (S2) After grinding and mixing asphalt and ZnCl2 in a mass ratio of 1:0.5, the mixture is placed in a muffle furnace and heated in air at a heating rate of 5°C / min, a heating temperature of 300°C, and a holding time of 8 hours. After cooling, a pretreated thermoplastic precursor is obtained.
[0034] (S3) Grind the pretreated particles in step (1) and step (2) into powder, weigh 90 parts by weight of the pretreated thermosetting precursor and 10 parts by weight of the pretreated thermoplastic precursor and place them in a ball mill, control the ball-to-material ratio to 20:1, set the ball mill speed to 450 rpm, forward and reverse modes, and ball mill for 4 hours to obtain a mixed precursor.
[0035] (S4) The mixed precursor is placed in a tubular furnace and calcined at a heating rate of 3°C / min to 600°C for 2 hours in an Ar atmosphere to obtain a pre-carbonized precursor, which is then ground and sieved to 200 mesh.
[0036] (S5) placing the above-mentioned mixed precursor in a high-temperature tubular furnace, calcining it in an argon atmosphere, with a heating rate of 10°C / min, heating to 1000°C and keeping it warm for 7 hours, cooling it to room temperature, and obtaining a hard carbon negative electrode material. The mixed precursor is calcined in a high-temperature tubular furnace, cooled to room temperature, ground, put into a hydrochloric acid solution and stirred for 24 hours, washed with deionized water, and dried to obtain a hard carbon negative electrode material.
[0037] Example 2
[0038] Other conditions and operations are the same as those in Example 1, except that in step (S5), the calcination temperature is changed from 1000°C to 1300°C.
[0039] Example 3
[0040] Other conditions and operations are the same as those in Example 1, except that in step (S5), the calcination temperature is changed from 1000°C to 1500°C.
[0041] Example 4
[0042] Other conditions and operations are the same as those in Example 1, except that in step (S5), the calcination temperature is changed from 1000°C to 1700°C.
[0043] Example 5
[0044] Other conditions and operations are the same as those in Example 1, except that in step (S5), the calcination temperature is changed from 1000°C to 2000°C.
[0045] Figure 1 This is a TEM image of the hard carbon material obtained in Example 1; Figure 2 This is a TEM image of the hard carbon material obtained in Example 2; Figure 3 This is a TEM image of the hard carbon material obtained in Example 3; Figure 4 is a TEM image of the hard carbon material obtained in Example 4; Figure 5 TEM image of the hard carbon material obtained in Example 5. It can be seen that the hard carbon material obtained in Example 1 exhibits a turbine-like structure, but the overall pseudo-graphite domain is short in length and no obvious closed-pore structure appears; when the carbonization temperature rises to 1300°C, the curved graphite domains in the hard carbon material obtained in Example 2 gradually become longer, and the accumulation produces a closed-pore structure with a pore diameter of about 1.3nm; as the carbonization temperature further increases, the closed-pore diameters produced by the hard carbon materials in Examples 3, 4, and 5 continue to increase, and when the carbonization temperature reaches 2000°C, the closed-pore diameter exceeds 5nm.
[0046] Example 6
[0047] The other conditions and operations are the same as those in Example 3, except that in step (S3), the thermosetting precursor is 80 parts by mass of pre-oxidized phenolic resin, and the thermoplastic precursor is 20 parts by mass of pre-oxidized asphalt.
[0048] Example 7
[0049] The other conditions and operations are the same as those in Example 3, except that in step (S3), the thermosetting precursor is 70 parts by mass of pre-oxidized phenolic resin, and the thermoplastic precursor is 30 parts by mass of pre-oxidized asphalt.
[0050] Example 8
[0051] The other conditions and operations are the same as those in Example 3, except that in step (S3), the thermosetting precursor is 60 parts by mass of pre-oxidized phenolic resin, and the thermoplastic precursor is 40 parts by mass of pre-oxidized asphalt.
[0052] Example 9
[0053] The other conditions and operations are the same as those in Example 3, except that in step (S3), the thermosetting precursor is 50 parts by mass of pre-oxidized phenolic resin, and the thermoplastic precursor is 50 parts by mass of pre-oxidized asphalt.
[0054] Example 10
[0055] The other conditions and operations are the same as those in Example 1, except that in step (S2), the asphalt is replaced by polyaniline, and the amount of the pretreated thermosetting precursor is 80 parts by mass, and the amount of the pretreated thermoplastic precursor is 20 parts by mass.
[0056] Embodiment 11
[0057] Other conditions and operations are the same as those in Example 6, except that in step (S1), the phenolic resin is replaced by an epoxy resin, and the amount of the pretreated thermosetting precursor is 80 parts by mass, and the amount of the pretreated thermoplastic precursor is 20 parts by mass.
[0058] Comparative Example 1
[0059] (S1) Phenolic resin and oxalic acid in a mass ratio of 1:0.2 are dissolved in ethanol, heated and stirred on a heating table at a temperature of 80° C. for 8 hours, and solidified particles are obtained after cooling.
[0060] (S2) Grinding the solidified particles into powder, placing them in a tube furnace for calcination, heating the temperature to 600° C. at a rate of 3° C. / min and maintaining the temperature for 2 hours in an Ar gas atmosphere to obtain a pre-carbonized precursor, which is then ground and sieved to 200 mesh.
[0061] (S3) The ground and sieved precursor is placed in a high-temperature tubular furnace and calcined in an argon atmosphere at a heating rate of 10°C / min. After the temperature is raised to 1500°C, it is kept warm for 7 hours and cooled to room temperature to obtain a hard carbon negative electrode material. The precursor is calcined in a hydrochloric acid solution and cooled to room temperature, ground, and stirred for 24 hours. The precursor is washed with deionized water and dried to obtain a hard carbon negative electrode material.
[0062] Comparative Example 2
[0063] (S1) After grinding and mixing asphalt and ZnCl2 in a mass ratio of 1:0.5, the mixture is placed in a muffle furnace and heated in air at a heating rate of 5°C / min, a heating temperature of 300°C, and a holding time of 8 hours. After cooling, pre-oxidized particles are obtained.
[0064] (S2) The pre-oxidized particles were placed in a tubular furnace and calcined at a heating rate of 3°C / min to 600°C for 2 hours in an Ar atmosphere to obtain a pre-carbonized precursor, which was then ground and sieved to 200 mesh.
[0065] (S5) The ground and sieved precursor is placed in a high-temperature tubular furnace and calcined in an argon atmosphere at a heating rate of 10°C / min. After the temperature is raised to 1500°C, it is kept warm for 7 hours and cooled to room temperature to obtain a hard carbon negative electrode material. The precursor is calcined in a hydrochloric acid solution and cooled to room temperature, ground, and stirred for 24 hours. The precursor is washed with deionized water and dried to obtain a hard carbon negative electrode material.
[0066] Comparative Example 3
[0067] The other conditions are the same as those in Example 6, except that oxalic acid is not added in step (S1).
[0068] Comparative Example 4
[0069] Other conditions are the same as those in Example 6, except that ZnCl2 is not added in step (S2).
[0070] Figure 6 is the small angle X-ray scattering spectrum of Example 3, Figure 7is the small angle X-ray scattering spectrum of Example 6; D and B" in the figure are the average pore size and pore number factor obtained by fitting the small angle X-ray scattering curve.
[0071] Application Examples
[0072] Preparation and testing methods of negative electrode materials: The hard carbon negative electrode materials, SuperP, and binder CMC / SBR obtained in the above embodiments and comparative examples are mixed in a mass ratio of 94:2:4, and an appropriate amount of water is added to make a slurry to obtain a uniformly mixed electrode slurry; the prepared electrode slurry is evenly coated on the carbon-coated aluminum foil, and after drying, it is vacuum-dried at 60°C for 12 hours and sliced; a metal sodium sheet is used as the counter electrode, a glass fiber is used as a diaphragm, and 1 mol / L NaPF6 (the solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) is used as the electrolyte, and a button battery is assembled in an argon-protected glove box. A constant current charge and discharge test is carried out, with a current density of 200mA / g and a charge and discharge voltage range of 0.001-2.0V. The test results are shown in Table 1.
[0073] Table 1 Electrochemical performance test of hard carbon negative electrode materials
[0074]
[0075] from Figure 1 It can be seen that the hard carbon material prepared in Example 1 exhibits a cross-linked turbine-shaped structure. However, due to the low carbonization temperature and the short length of the carbon layer, a closed-cell structure is difficult to form in the cross-linked structure, which cannot provide ideal conditions for the formation of metalloid sodium. Figure 2 It is shown that when the carbonization temperature is increased to 1300 °C, the hard carbon material exhibits a clear graphite-like layer structure, and these layers are cross-linked to form a closed-pore structure. Figure 3 , Figure 4 and Figure 5 It is further shown that as the carbonization temperature increases further, the length of the graphite-like domain increases significantly, the closed pore size increases continuously, and finally a closed pore structure with a pore size of up to 5 nm is formed when the carbonization temperature reaches 2000°C. These larger closed pore structures are conducive to the growth of pseudo-sodium metal clusters. However, higher carbonization temperatures also lead to a narrowing of the carbon layer spacing, reducing the diffusion rate of sodium ions; at the same time, the growth of larger pseudo-sodium metal clusters greatly limits the sodium storage kinetics in the platform region, which is not conducive to the rate performance of the material.
[0076] Figure 6 and Figure 7 The small angle X-ray scattering spectra of Example 3 and Example 6 are shown, and the correlation factor between the closed cell diameter and the number of closed cells is fitted and calculated. The fitting formula is as follows:
[0077]
[0078] Where I is the scattering intensity as a function of Q; Q is the scattering amount; A is the surface scattering factor at low Q; B is the scale factor of pore scattering, which is proportional to the pore surface area; a0 is the correlation factor with the pore size R, a0 = R × 10 -0.5 ; D is the background height.
[0079] from Figure 6 and Figure 7 It can be seen that when a small amount of thermoplastic precursor is added, the hard carbon material exhibits a larger closed pore size, but the number of closed pores is small; when the proportion of thermoplastic precursor is increased, the closed pore size in the hard carbon material decreases from 3.11nm to 1.69nm, but the pore number correlation factor increases from 0.064 to 0.225. This shows that the addition of thermoplastic precursors can slow down the increase of closed pore size, thereby forming more small pores at higher carbonization temperatures. The formation of these small pores helps to achieve rapid sodium storage in the platform area.
[0080] It can be seen from Table 1 that the sodium storage capacity of the hard carbon material at 20mA / g will not increase with the increase of the closed pore diameter. On the contrary, when the closed pore diameter increases to a certain extent, the sodium storage capacity will decrease; and the rate performance of the hard carbon material will also decrease with the increase of the closed pore diameter. For example, the hard carbon material prepared in Example 1 has good rate performance, and the capacity retention rate at a current density of 200mA / g is 75.7%, but due to the small number of pores, the overall capacity is low. When the carbonization temperature is increased to 1500°C, the closed pore diameter of the hard carbon material prepared in Example 3 increases to 3.1nm, and the capacity is increased to 346.8mAh / g, but its rate performance is poor, and the capacity retention rate at 200mA / g is only 33.8%. When the proportion of thermoplastic precursor is increased, the closed pore diameter of the hard carbon material prepared in Example 6 is smaller, but the number of pores is larger, showing a capacity of 400.4mAh / g and a capacity retention rate of 88.4%.
Claims
1. A method for preparing a fast-charging hard carbon negative electrode material, characterized in that: The following steps are involved: (S1) mixing a metal chloride with a thermoplastic precursor, and heating and keeping the mixture in an oxygen-containing atmosphere to obtain a pretreated thermoplastic precursor; The thermosetting precursor and the acidic curing agent are subjected to curing treatment to obtain a pretreated thermosetting precursor; (S2) mixing the pretreated thermoplastic precursor and the pretreated thermosetting precursor uniformly, and pre-carbonizing them under an inert atmosphere; Then, the hard carbon material is obtained by high-temperature carbonization in an inert atmosphere or a hydrocarbon gas atmosphere; the pretreated thermosetting precursor accounts for 50-90% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor.
2. The preparation method according to claim 1, characterized in that: In step (S1), the thermoplastic precursor is selected from at least one of polyvinyl chloride, polyaniline, asphalt, coal, and petroleum coke; the metal salt chloride is selected from at least one of NaCl, KCl, ZnCl2, MgCl2, and CaCl2; preferably, the mass ratio of the thermoplastic precursor to the metal salt chloride is 1:0.5-1.
3. The preparation method according to claim 1, characterized in that: In step (S1), the thermosetting precursor is selected from at least one of phenolic resin, epoxy resin, sucrose, cellulose, and cotton; the acidic curing agent is selected from at least one of oxalic acid, phosphoric acid, benzenesulfonic acid, tartaric acid, citric acid, and anhydrous benzoic acid; preferably, the mass ratio of the thermosetting precursor to the acidic curing agent is 1:0.1-0.
3.
4. The preparation method according to claim 1, characterized in that: In step (S1), the oxygen-containing atmosphere refers to an atmosphere having an oxygen content greater than 20%, such as air, oxygen, or a mixture of air and oxygen; the temperature is raised to 200-300° C. at a heating rate of 2-10° C. / min and maintained for 5-10 hours.
5. The preparation method according to claim 1, characterized in that: In step (S2), the pretreated thermosetting precursor accounts for 60-80% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor; preferably, the pretreated thermosetting precursor accounts for 70-80% of the total mass of the pretreated thermosetting precursor and the pretreated thermoplastic precursor.
6. The preparation method according to claim 1, characterized in that: The thermosetting precursors are phenolic resin and epoxy resin, and the thermoplastic precursor is asphalt.
7. The preparation method according to claim 1, characterized in that: In step (S2), the uniform mixing method includes ball milling, grinding, and sand milling; preferably, ball milling, with a ball-to-material ratio of 10-20:1, a rotation speed of 400-700 rpm, and a ball milling time of 3-10 hours.
8. The preparation method according to claim 1, characterized in that: In step (S2), the pre-carbonization is carried out under an inert atmosphere, the temperature is raised to 500-800°C and kept for 2-5 hours, the inert atmosphere is under an argon atmosphere, and the heating rate is 1-3°C / min; the inert atmosphere is at least one of nitrogen and argon.
9. The preparation method according to claim 1, characterized in that In step (S2), the high temperature carbonization is carried out by heating the temperature to 1000-1700°C, preferably 1300-1500°C, at a heating rate of 5-10°C / min, and calcining for 5-10 hours.
10. The present invention also provides a negative electrode material for a sodium ion battery, comprising a hard carbon material, a conductive additive, and a binder, wherein the hard carbon material is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sodium-ion battery hard carbon negative electrode material and preparation method thereof
CN116022769A
Hard carbon cathode material for lithium ion power and energy storage battery and preparation method of hard carbon cathode material
CN103094528A
Nitrogen-doped hard carbon material, preparation method thereof and application of nitrogen-doped hard carbon material in negative electrode of sodium-ion battery
CN116425140A